2021
DOI: 10.3390/foods10102340
|View full text |Cite
|
Sign up to set email alerts
|

Cocoa (Theobroma cacao L.) Seed-Derived Peptides Reduce Blood Pressure by Interacting with the Catalytic Site of the Angiotensin-Converting Enzyme

Abstract: This study aimed at determining the effect of cocoa proteins (CP) on the blood pressure, using in silico, in vitro and in vivo approaches. The in silico assay showed 26 Criollo cocoa peptides with alignment in the Blast® analysis. Peptide sequences ranged from 6 to 16 amino acids, with molecular weight ranging from 560.31 to 1548.76 Da. The peptide sequences LSPGGAAV, TSVSGAGGPGAGR, and TLGNPAAAGPF showed the highest theoretical affinity with −8.6, −5.0, and −10.2 kcal/mol, for the angiotensin-converting enzym… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 50 publications
(64 reference statements)
0
9
0
Order By: Relevance
“…Moreover, Coronado‐Cáceres et al . (2021) reported that cocoa proteins subjected to SGD presented ACE inhibition with an IC 50 value of 0.49 mg mL −1 and reduced 5% systolic blood pressure and 7% diastolic blood pressure in rats administered with a high‐fat diet.…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, Coronado‐Cáceres et al . (2021) reported that cocoa proteins subjected to SGD presented ACE inhibition with an IC 50 value of 0.49 mg mL −1 and reduced 5% systolic blood pressure and 7% diastolic blood pressure in rats administered with a high‐fat diet.…”
Section: Resultsmentioning
confidence: 99%
“…This is the case of intestinal digests of quinoa, which showed antihypertensive effects in spontaneously hypertensive rats and ACE inhibitory action specifically associated with FHPFPR, NWFPLPR, and NIFRPF peptides [ 117 ]. Likewise, the specific peptides obtained from simulated digesta of cocoa seed protein, namely, LSPGGAAV, TSVSGAGGPGAGR, and TLGNPAAAGPF, showed ACE inhibitory and antihypertensive activity in a high-fat diet rat model [ 122 ].…”
Section: Production Of Bioactive Peptides Derived From Underutilized ...mentioning
confidence: 99%
“…This paper aimed to explore the potential of peptides which inhibit pancreatic lipase obtained from the natural world as an anti-obesity therapeutic approach. For instance, pancreatic lipase inhibitory peptides have been obtained from plantbased sources i.e., millet grain [7], rice bran [8], oat bran [9], cocoa protein hydrolysates [10], cumin seeds [11], spent brewer's grain [12], hazelnuts [13], soybeans [14], fermented beans [15], and onions [16]. On the other hand, pancreatic lipase inhibitory peptides have been derived from marinebased sources such as sea cucumbers [17], tuna fish [18], shark fish [19], miiuy croaker fish [20], and dried seaweed-spirulina [21].…”
Section: Introductionmentioning
confidence: 99%
“…Likewise, in-silico evaluations of potential drug-like inhibitors of pancreatic lipase involved the SwissADME prediction tool, semi-empirical quantum mechanics (SQM), molecular electrostatic potential (MEP) and molecular docking analysis. Their chemical reactivity and detailed molecular interactions of identified compounds with pancreatic lipase at its catalytic site domain were also elucidated and discussed [10,18] . Collectively, these reports illustrate few of the remarkably origins for peptide drug discovery and development.…”
Section: Introductionmentioning
confidence: 99%